Aerodynamic optimisation of a small-scale wind turbine blade for low windspeed conditions - Cencelli, Nicolette Arnalda (Stellenbosch : Stellenbosch University, 2010)
Thesis (MScEng (Department of Mechanical and Mechatronic Engineering))--Stellenbosch University, 2006.